The Effects Of Cigarette Smoking On The Serum Levels Of Some Antioxidants (Vitamin C And E ) Amongst Male Smokers In Levels In College Of Health Sciences, Nnamdi Azikiwe University, Nnewi Campus, Anambra State - Ekenedilichukwu, Okwara John; Chukwuemeka Solomon, Ibe; Chukwuemeka, Ogbodo Emmanue; Rosemary Adamma, Analike; Onyema Athanatius, Onyegbule; Nwabunwanne, Oguaka Victor; Akuma Kalu, Amah; Timothy Uzoma, Mbaeri; Chukwuemeka, Meludu Samuel (International Journal of Scientific Research and Management (IJSRM), 2018)
Smoking has been identified as one of the major risk factors in human diseases such as atherosclerosis and several cancers. This study investigated the effect of smoking on vitamin C and E levels in male cigarette smokers in College of Health Sciences, Nnamdi Azikiwe University, Nnewi Campus, Anambra State. A total of 100 subjects comprising of (50 smokers and controls) each were recruited for the study. A well structured questionnaire was used in obtaining the demographic and anthropometric data as well as dietary pattern of subjects. Thereafter, 5mls of blood sample was collected from subjects and used for the evaluation biochemical parameters. Biochemical parameters (vitamin C and E levels) were estimated using standard methods and results subjected to statistical analysis using student t-test and Pearson r correlation. The results show a significant decrease in the mean serum levels of Vitamins C (0.82±0.33 vs 1.49±0.25; p=0.000) and E (12.36±1.61 vs15.61±1.91; p=0.000) in smokers compared with non smokers respectively. More so, there was a significant positive correlation between BMI and serum level of Vitamin C (r=0.345; P=0.014) and E (r=0.187; P=0.024) in cigarette smokers. In conclusion, the study revealed the deleterious effects of cigarette smoking on serum levels of vitamins C and E in smokers. Hence, there is need for proper dietary management in patients.